Relationship between drivers of performance in smaller firms. - Zulkifli, Norzima; Mohd Yusuff, Rosnah; Sorooshian, Sharyar; Ismail, Mohd Yusof (2011)
This study builds a structural model for a generic theory of business success in the SME-context, based on literature from the areas of strategic management and small business management, as well as performance measurement and on empirical evidence from experts. The paper starts by discussing the importance of SME performance study and end the writing with a conceptual model on relationship between strategic management drivers and performance of smaller firms. The prediction ability of this SME performance study is also discussed here as this research result.